The global research trends and hotspots on phthalate esters (PAEs): A comprehensive visualization and bibliometric analysis (2000-2023) - Yajun Hong; Sizhe Zhang; Zhenfei Yan; Saraschandra Naraginti; Meiqing Zhu; Dayong Xu (Environmental Chemistry and Ecotoxicology, 2025)
Phthalate esters (PAEs) have garnered significant interest over the last twenty years due to their widespread presence and substantial environmental hazards. Nevertheless, absence of a complete bibliometric study of recent advances and trends in research on PAEs. This paper aims to fill this gap by offering an in-depth analysis of 7069 PAEs-related articles published from 2000 to 2023, highlighting research progress, emerging trends, and key themes. From 2012 to 2023, the number of publications on PAEs surged, reflecting a growing focus within Environmental Sciences. Current research topics predominantly encompass pollution surveys, characterization, spatial distribution, and risk identification, with ecological risk assessment emerging as a prominent research area between 2012 and 2021. China and the United States are the most influential countries according to total publications, total citations and average citations per article, while the Chinese Academy of Sciences and the United States Environmental Protection Agency were identified as leading institutions. PAEs levels in Chinese waters and sediments were notably higher compared to other nations. PAEs present significant risks to human health and ecological systems, necessitating serious attention. This research gives an objective and comprehensive summary of the current situation of PAEs research and suggests future directions for scholars in this domain.